Gestión estratégica y su incidencia en la ventaja competitiva de la librería y papelería Mundoffice, Quevedo año 2024. - Moncayo Castro, Leonor Magdalena (2025)
Lack of awareness of efficient strategic management practices leads bookstores and stationery stores to lack a clear organizational mission and vision. MundOffice Bookstore and Stationery Store, located in Quevedo Canton, its main headquarters and with several branches in neighboring cantons, as well as in Guayaquil and Quito, has experienced several setbacks due to economic downturn, logistics, and technological adjustment, resulting in a weak market positioning and poor adaptability to contingencies. The objective of this research was to analyze the strategic management applied to improve competitive advantages at MundOffice Bookstore and Stationery Store in Quevedo Canton. The methodology applied was a mixed approach, allowing for the collection of individual information and its tabulation as a whole, using the deductive-inductive method. It described generalities of the study population.